Collocations in a learner corpus - Nesselhauf, Nadja (John Benjamins Publishing Company, 2004)
Collocations are both pervasive in language and difficult for language learners, even at an advanced level. In this book, these difficulties are for the first time comprehensively investigated. On the basis of a learner corpus, idiosyncratic collocation use by learners is uncovered, the building material of learner collocations examined, and the factors that contribute to the difficulty of certain groups of collocations identified. An extensive discussion of the implications of the results for the foreign language classroom is also presented, and the contentious issue of the relation of corpus linguistic research and language teaching is thus extended to learner corpus analysis.